Pengelolaan Hutan Dalam Rangka Otonomi Daerah oleh Pemerintah Aceh Utara - Arnita Arnita (Kanun Jurnal Ilmu Hukum, 2013)
ABSTRACT: A district government is trying to attract authority of the governmental management into the region especially that can increase the original revenue shortly, for instance a forest management authority. Despite the Act Number 41, 1999 regarding Forestry has been passed but the Government Regulation has not followed it. Thus, the government has no any clear reference in determining the forest management in the area. District body can do the management independently and it can also be submitted to the third party in some kinds of management. The Regional Forestry Department as similar to other regional departments, even it has been joined with other departments, its duty seems administratively only. Thus, it requires the establishment of the Forest Management Unit that can manage the forest directly. The body is better established in sort of the United of Forest Authority that is divided into the Part of the United Forest Authority then minimizes into the Resort of Forestry Police and it is done for all forms or functions of forest area that is not submitted its management to the third party. The Unit provides all activities planning of forest including annual logging included into annual working planning. Forest Management in Terms of Regional Autonomy by Aceh Utara Government